2013
DOI: 10.1002/app.39307
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and dielectric properties of short‐carbon‐fibers/epoxy‐modified‐organic‐silicone‐resin as heat resistant microwave absorbing coatings

Abstract: Heat resistant microwave absorbing coatings were prepared by brushing and thereafter heat treatment, using epoxy modified organic silicone resin as binding material, short carbon fibers (C sf ) as absorbers, talcum powder and glass powder as filling materials. The mechanical and dielectric properties of the coatings before and after heat treatment at 600 C for 10 mins were studied. The results showed that the adhesive power after heat treatment enhances remarkably, both the real (e 0 ) and imaginary (e 00 ) pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…CNTs have many advantages such as strong microwave absorption properties in a wide gigahertz frequency range, low density, good compatibility, and corrosion resistance which make CNTs ideal materials for EMI shielding and microwave absorption . Although the use of CNTs on the EMI shielding and microwave absorbing materials has been conducted in the literature, most of the dispersion methods employed are either US or mechanical stirring methods which may form agglomerates and may not reflect the advantage of CNTs' microwave properties. To the best of authors' knowledge, the effect of dispersion and microstructures of CNTs on the complex permittivity and microwave absorptivity of CNT/epoxy composite absorbers in 2−18 GHz has rarely been revealed and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…CNTs have many advantages such as strong microwave absorption properties in a wide gigahertz frequency range, low density, good compatibility, and corrosion resistance which make CNTs ideal materials for EMI shielding and microwave absorption . Although the use of CNTs on the EMI shielding and microwave absorbing materials has been conducted in the literature, most of the dispersion methods employed are either US or mechanical stirring methods which may form agglomerates and may not reflect the advantage of CNTs' microwave properties. To the best of authors' knowledge, the effect of dispersion and microstructures of CNTs on the complex permittivity and microwave absorptivity of CNT/epoxy composite absorbers in 2−18 GHz has rarely been revealed and investigated.…”
Section: Introductionmentioning
confidence: 99%
“…They have studied the electromagnetic properties as well as mechanical properties after heat treatment (600 °C for 10 min), and it is found that the mechanical properties of the coating has been improved but it does not alter the EM properties. This coating can be used for high temperature RAS for 10 min . Mandal and Das has also developed thermally stable nano composites using Cobalt doped Ni‐Zn ferrites and nanoparticles of barium titanate in epoxy matrix.…”
Section: Introductionmentioning
confidence: 99%
“…This coating can be used for high temperature RAS for 10 min. 38 Mandal and Das 39 has also developed thermally stable nano composites using Cobalt doped Ni-Zn ferrites and nanoparticles of barium titanate in epoxy matrix. The nanoparticles were synthesized using co-precipitation and hydro thermal method.…”
Section: Introductionmentioning
confidence: 99%